Novel exploitation of cold atom experimental techniques for the development of Quantum Technologies - Johnson, David (2024)
Ultracold atom experiments permit a wide range of applications within the field of quantum technologies by studying atom - photon interactions at micro kelvin temperatures. Cold atom systems are already used in a variety of fields including developing quantum computers, high precision sensors such as magnetometers and gravimeters, tests of fundamental physics in luding detecting dark matter and tests of quantum gravity and many, many more.